Temporary Protection in Europe After 1990: The “Right to Remain” of Genuine Convention Refugees - Davor Sopf (Washington University Journal of Law & Policy, 2001)
This Essay addresses problems inherent in the application of temporary protection to the large number of genuine 1951 Convention refugees from Bosnia -Herzegovina.
Keywords: Political refugees; Repatriation; Refugees -- Europe; Yugoslav War, 1991-1995